Shifting from Conventional Curriculum to Value-based Medical Curriculum: Narrative Review - Shrivastava Prateek Saurabh; Tiwade Yugeshwari (Wolters Kluwer Medknow Publications, 2024)
Value-based medical education is essential for the provision of quality-assured patient-centered healthcare services. The purpose of the current review is to explore the need for the adoption of a value-based approach in medical curriculum, identify the merits, devise a stepwise plan for the implementation of a value-based curriculum, and identify the potential concerns and the strategies to overcome them. The implementation of a value-based approach in medical curricula requires a systematic and stepwise approach to ensure the attainment of maximum benefits. However, this implementation can be accompanied by multiple challenges, and we will require the active involvement of medical educators and college administrators to overcome them. The delivery of value-based medical education is expected to prepare the future cohort of healthcare professionals to deliver patient-centered care. This calls for the need to adopt a multipronged approach to ensure that this value-driven teaching is integrated into the existing model of delivery of medical education, as it will significantly improve patient outcomes and well-being.